Large igneous provinces linked to supercontinent assembly - Wang, Yu; Santosh, M.; Luo, Zhaohua; Hao, Jinhua (Journal of geodynamics, 2015)
•The coeval nature of the continental flood basalt eruptions with the timing of assembly of the supercontinent Pangea.•The formation of large igneous provinces in the absence of plumes rising up.•New model correlates the large igneous provinces to lithospheric extension caused by asthenospheric flow. Models for the disruption of supercontinents have considered mantle plumes as potential triggers for continental extension and the formation of large igneous provinces (LIPs). An alternative hypothesis of top-down tectonics links large volcanic eruptions to lithospheric delamination. Here we argue that the formation of several LIPs in Tarim, Yangtze, Lhasa and other terranes on the Eurasian continent was coeval with the assembly of the Pangean supercontinent, in the absence of plumes rising up from the mantle transition zone or super-plumes from the core–mantle boundary. The formation of these LIPs was accompanied by subduction and convergence of continents and micro-continents, with no obvious relation to major continental rifting or mantle plume activity. Our model correlates LIPs with lithospheric extension caused by asthenospheric flow triggered by multiple convergent systems associated with supercontinent formation.